PENGGUNAAN MEDIA PERMAINAN ULAR TANGGA PADA PEMBELAJARAN PIPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PEMBAGIAN WILAYAH WAKTU DI INDONESIA - Dewi, Tipani Liani; Kurnia, Dadang; Panjaitan, Regina Lichteria (Jurnal Pena Ilmiah, 2017)
Based on the unsatisfactory result of the study of students of class V SDN Sindang I on the material division of time region in Indonesia is arranged by using the snake laddergame mediaso that the learning more interesting through classroom action research (PTK) with Kemmis and Taggart design consist of planning, implementation, observation, and reflection. Instruments used, the observation patterns of teacher performance and student activieties, student learning outcomes, field notes, and vision of teacher and students. Complete study result of 29 students at initial data only 10 students (34,5%), then cycle I to 23 students (79,3%), cycle II increased to 25 students (86,2%), in the third cycle reached the target with 27 students (93,1%) complete the achievement of KKM. So, learn by using the snake ladder game media results of learning improvement class V SDN Sindang I on the material division of time region in Indonesia.